Perolehan Semantik Anak Usia 0;0-2;0 Tahun pada Masa Sensorik-Motorik - Fauzana, Pitria Wahyu; Ermanto, Ermanto; Basri, Irfani (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This article was written to determine acquisition of semantic olds 0;0-0;2 to word class noun, verbs, and adjectives. This research method is descriptive method. Research findings are; firts, child has mastered noun 121 words, consisting of noun limb, noun of objects arround, noun of fruits, noun of animal, noun of greeting, and noun of substance secreted human.second, childs has mastered 35 words of verb, consisting of action verbs, process verb, and state verbs. Third, child has mastered 50 words of adjectives, consisting of trait adjectives, size, feeling, time, distance,senses, form, and colour.